DATA LOSS PREVENTION USING POST QUANTUM CRYPTOGRAPHY: OVERVIEW OF ROUND-3 ALGORITHMS - Augustine Chidiebere Onuora; Prince Ana; Anthony O Otiko; Chibuike Ezeocha Madubuike (STMIK Pringsewu Lampung, 2021)
The current hype of quantum computing has necessitated the need for computer security stakeholders to call for the design of security algorithms that will be quantum efficient when quantum computers finally grace our computing sphere. Recent advancements in quantum computing have made cryptographic schemes more vulnerable to quantum attacks like Shor’s algorithm and Grove’s algorithm. Therefore NIST call for a new set of algorithms known as Post-Quantum cryptography that would be quantum proof is imminent. Many Post quantum algorithms have been designed and tested. But only few of them made it to the round 3 (the final round). This paper reviewed these post quantum candidates. Literatures highlighting their scheme, properties, implementation and areas of security coverage was reviewed. Recommendations on future research areas in this field was itemized for this novel security paradigm as we await the final standardization of this cryptosystems.